THE EFFECT OF MARKETING COMMUNICATION STRATEGY ON BRAND LOYALTY: THE MODERATING ROLE OF CUSTOMER BRAND ENGAGEMENT ON CUSTOMERS OF BANK PEREKONOMIAN RKYAT? - Fiyah Agustin Hakim; Yolanda Masnita; Kurniawati Kurniawati; Harno Diansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The microbanking sector, particularly Rural Banks (Bank Perekonomian Rakyat – BPR) in Indonesia, is currently facing increasing challenges, including regulatory pressures and declining customer trust. These conditions have created a competitive environment where maintaining brand loyalty becomes essential for sustainability. This study aims to analyze the influence of marketing communication strategies, namely Advertising, Public Relations, Direct Marketing, and Sales Promotion, on Brand Loyalty, with Customer Brand Engagement acting as a moderating variable. A quantitative approach was employed using a survey method, with data collected from 210 respondents through convenience sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Advertising does not have a direct significant effect on Brand Loyalty, but it significantly influences Customer Brand Engagement. Customer Brand Engagement has a strong and significant effect on Brand Loyalty and mediates the relationship between Advertising and Brand Loyalty. Meanwhile, Direct Marketing shows a marginal effect, while Public Relations and Sales Promotion do not significantly influence Brand Loyalty. These findings highlight the importance of engagement-based marketing strategies in enhancing brand loyalty. Rural Banks should prioritize customer engagement initiatives to strengthen emotional connections and improve long-term customer relationships.